Pengaruh Penyuluhan Menggunakan Video Interaktif Terhadap Pengetahuan Menyikat Gigi Dengan Teknik Roll Pada Siswa SDN Sukalangu 3 Kabupaten Pandeglang - Husna, Naila Fatihatul; Widyastuti , Tri; Heriyanto, Yonan; Utami, Ulfah (Poltekkes Kemenkes Bandung, 2024)
The first step in preventing oral and dental disease is to maintain oral hygiene, by brushing your teeth. This behavior must be taught from an early age for the realization of a better health status. Objective: To determine the effect of counseling using interactive videos on knowledge of brushing teeth with the roll technique in elementary school students. The type of research conducted was analytic, with a pre experiment method with a one group pretest-posttest design. sampling using total sampling of 74 students. The variables in the study were Interactive Video and elementary school students' knowledge. Interactive Video has been tested and deemed feasible by media and material experts. Hypothesis testing using the Wilcoxon sign rank test. The average score of tooth brushing knowledge with the roll technique before counseling in classes I, II, III was 41.25, after counseling it was 68.25. In class IV,V,VI before counseling was 42.35, after counseling became 70.59. Wilcoxon Sign Rank Test analysis shows p-value (0.000) <0.05, there is a significant influence between before and after counseling using interactive videos on tooth brushing knowledge.The results of this study indicate that interactive videos can increase tooth brushing knowledge to elementary school students. So that students will better maintain the cleanliness of their teeth. In conclusion, counseling using animated interactive video media can affect the knowledge of brushing teeth with the Roll technique in students.